AN ANALYSIS OF STUDENTS' ABILITY IN WRITING NARRATIVE TEXT IN ENGLISH ONLINE LEARNING OF THE TENTH GRADE SMKN 1 PACITAN - Filda Dwi Ristyaningrum; Dwi Rahayu; Hasan Khalawi (English Education Study Program STKIP PGRI Pacitan, 2022)
Writing is one type of skill that students must master. Based on the research of the researcher, this issue had not been investigated by others. The objectives of the research are to find out the dominant problem found in the writing ability indicators. In this research, the researcher used the qualitative descriptive method. The data collecting techniques used in this research are tests and interviews. Subjects of this research were 29 students of X TB 1 at SMKN 1 Pacitan. This research finding showed that the mean score of students' writing ability is 61.55. The researcher showed that the X TB 1 SMKN 1 Pacitan has a fairly good competence from their ability to write narrative texts in learning English. As a result of the test, there were 5 students (25%) who got score 70- 84 (Good to Average), 10 students (50%) got to score 55-69 (Fair to Poor), 5 students (25%) got to score 25-54 (Very Poor). Most of them cannot write the correct spelling, using punctuation and capital letters. Students cannot have good ideas, lack motivation, lack support from parents so that students do not have the determination to reach better grades. Students are not interested in writing narrative text. Based on the results, the researcher would like to suggest that teachers pay closer attention to improving the process of teaching writing English. Students are expected to be more active in participating in activities to improve their writing skills during and outside the classroom.